Early recruitment of coronary collateral circulation: impact in late presentation nonreperfused acute coronary occlusion. Issue 7 (November 2018) - Gutiérrez-Barrios, Alejandro; Cañadas-Pruaño, Dolores; Bretones-Del Pino, Teresa; Alba-Sánchez, Miguel; Ruiz-Fernández, Dolores; Calle-Perez, Germán; Agarrado-Luna, Antonio; Zayas-Rueda, Ricardo; Marante-Fuertes, Ernesto; Giráldez-Valpuesta, Alberto; Oneto-Otero, Jesús; Vázquez-García, Rafael
Abstract : Background: Debate still remains on whether the presence of early recruited collateral circulation (ERCC) in the setting of an acute coronary occlusion (ACO) has a prognosis benefit. Some previous reports have shown lower mortality and morbidity rates in well-collateralized patients compared with those with poorly recruited collateral circulation (PCC), but others have not. In the primary angioplasty era, the role of collateral circulation in these studies may have been influenced by the effect of early reperfusion. The actual impact of ERCC in ACO can be clarified by studying its effect on nonreperfused patients. Objective: This study aimed to compare the 1-year clinical outcome in nonreperfused late presentation ACO in a major coronary artery with ERCC versus PCC. Patients and methods: Between 2008 and 2015, we included 164 patients with a nonreperfused late presentation ACO. The patients were divided according to the presence of angiographic ERCC (Rentrop 2–3) or PCC (Rentrop 0–1). ERCC was present in 54% of patients. Patients with ERCC less often presented with cardiogenic shock ( P =0.02) and the right coronary artery was the most frequent culprit vessel ( P =0.02). The presence of PCC was associated independently with higher 1-year cardiovascular mortality [hazard ratio (HR): 6.92; 95% confidence interval (95%CI): 1.37–34.7; P =0.019], 1-year total mortality (HR: 5.79; 95%CI: 1.95–17.1; P =0.001), and 1-year major adverse cardiac event (HR: 8.05; 95%CI: 1.73–37.4; P <0.01). Conclusion: The presence of angiographically PCC in the setting of late presentation nonreperfused ACO is relatively infrequent (46%) and is associated with worse 1-year major clinical outcomes.